Assessment on Water Resource Management for Sedawgyi Dam: A WEAP Analysis Approach - Htoo, Thet Zin; Yin Yin Htwe; Cho Cho Thin Kyi (AI Society & STMIK Indonesia, 2024)
This study employs the Water Evaluation and Planning (WEAP) system to analyze water resource management for the Sedawgyi Dam in Myanmar. The research integrates hydrological data, demand projections, and infrastructure information to simulate current and future water scenarios. Key steps include model setup, calibration, scenario development, and analysis. The results indicate that Mandalay City's highest domestic water demands are in Chanmyatharzi and Aungmyaetharzan townships, with agricultural water demands peaking in Mattaya township. The reference scenario highlights a significant domestic water supply shortfall, meeting only 10% of the demand, while agricultural demands are nearly fully met. The study underscores the urgent need for improved water management strategies to address rising unmet water demands, particularly for domestic use, to ensure sustainable water resource allocation in the region.